200k views
2 votes
9. Given that 2(x - 4) - 9 = 17, you can prove that: A. X=0 B. X = 2 C. x = 15 D. x = 16 E. None of the above

1 Answer

2 votes

Answer:

E. None of the above.

Explanation:

We have to solve the expression for x. First we solve the parenthesis and then we continue adding similar terms.


2(x-4)-9=17\\2x-8-9=17\\2x-17=17\\2x=17+17\\2x=34\\x=34/2\\x=17

Therefore, x = 17.

We don't have that option among the first 4 options, therefore the correct answer would be E. None of the above.

User Maximum
by
4.7k points